Blepharoptosis and HAART Related Mitochondrial Myopathy. (December 2014) - Chapman, Kristin Ow; Lelli, Gary
Abstract Purpose: To report a case of blepharoptosis in a patient with human immunodeficiency virus (HIV) on highly active antiretroviral therapy (HAART) with biopsy confirmed mitochondrial deletions consistent with HAART related myopathy. Methods: A 51-year-old man with HIV demonstrated visually significant ptosis after being on HAART therapy for over 20 years. Results: Muscle tissue biopsy following blepharoplasty was analyzed and found to have significant mitochondrial deletions. Conclusions: This patient represents a case of isolated ptosis consistent with acquired myopathy secondary to mitochondrial dysfunction without systemic manifestations otherwise seen in inherited mitochondrial disorders.